Curriculum Review Of Fun School Movement - oktavia, maya veri; Widodo, Hendro (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
Some individuals of education have agreed to state that the heart of education is in the curriculum. A curriculum contains many constructive elements so the learning runs optimally. A national curriculum that is the basic guidelines for a task force to develop a curriculum that allows for educational programs to adapt to the local needs and potential. This main goal of this research was to know extensively and describe the curriculum of fun School movement . This research have used qualitative description method that can give  result of in- depth- theoretically analysis. Through the fun school movement implementation, Muhammadiyah Bausasran Yogyakarta elementary school compiled a regular school curriculum combined with curriculum 2013. The application of GSM curriculum  impacts to substraction of bullying cases dan embodiment of fun learning atmosphere.